Performance Evaluation of Principals of Public Elementary Schools - Prasetyo, Aris Kukuh; Dwikurnaningsih, Yari (International Journal of Elementary Education, 2020)
This study aimed to evaluate the performance of public-school principals in Tuntang District. The subjects of this study were the heads of SD Negeri 01 Tomplakan and SDN Tlompakan 03 using qualitative data collection techniques through interviews and observations. Data triangulation using technique triangulation and source triangulation. Triangulation of techniques through interviews, documentation studies, and observations. Triangulation of sources from the results of interviews of principals was matched with the results of interviews of supervisors, teachers, and school committees, with the same questioning instrument. The data analysis technique used is qualitative with qualitative interview data from research results at SD Negeri 01 Tomplakan out of 13 competencies, 10 competencies are able, and 3 competencies that are less capable while SDN Tlompakan 03 there are 11 capable competencies and 2 competencies that are less able. The ability of principals to the maximum is in aspects of developing school planning, developing organizations, leading schools, creating a conducive school culture, management of teachers and staff, infrastructure, community relations, managing students, curriculum and special service units, information systems, and monitoring evaluation. Conclusions from this study the headmaster has been able to carry out his managerial competence well despite having to improve his administration and use of IT in schools. Recommendations from the results of this research that are "poor" need to be improved by adding administrative staff in elementary schools and conducting training in the use of IT.